2021
DOI: 10.1002/ijc.33443
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii infection and the risk of adult glioma in two prospective studies

Abstract: Toxoplasma gondii (T gondii) is a common parasite that shows affinity to neural tissue and may lead to the formation of cysts in the brain. Previous epidemiologic studies have suggested an association between glioma and increased prevalence of T gondii infection, but prospective studies are lacking. Therefore, we examined the association between prediagnostic T gondii antibodies and risk of glioma in two prospective cohorts using a nested case‐control study design. Cases and matched controls were selected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Although the parasite forms cysts preferentially in the brain and a variety of brain cells, including astrocytes and neurons, can be infected, the relationship between T. gondii infection and brain tumors is scarcely described in the literature [ 30 ]. Schuman et al showed that astrocytoma patients were significantly more likely than controls to have antibodies to T. gondii [ 20 ], and there is some prospective evidence of an association between T. gondii infection and risk of glioma [ 31 ]. Moreover, in epidemiological studies, T. gondii seropositivity among brain tumor patients (18.3%) was significantly ( p < 0.05) higher than that of healthy controls (8.6%) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the parasite forms cysts preferentially in the brain and a variety of brain cells, including astrocytes and neurons, can be infected, the relationship between T. gondii infection and brain tumors is scarcely described in the literature [ 30 ]. Schuman et al showed that astrocytoma patients were significantly more likely than controls to have antibodies to T. gondii [ 20 ], and there is some prospective evidence of an association between T. gondii infection and risk of glioma [ 31 ]. Moreover, in epidemiological studies, T. gondii seropositivity among brain tumor patients (18.3%) was significantly ( p < 0.05) higher than that of healthy controls (8.6%) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…(continued) In a relatively small study of serum samples from two separate cohorts antibodies to T. gondii were significantly associated (OR: 2.70; 95% CI: 0.96-7.62; OR: 1.32, 95% CI: 0.85-2.07) with glioma risk before diagnosis, eliminating reverse causation biasing the association[52]. Further serologic studies examining T. gondii are needed.…”
mentioning
confidence: 99%
“…A recent meta-analysis that included all 16 studies, with 3771 epileptic patients and 4026 healthy controls, reported an odds ratio of 1.72, p = 0.001 [91,92]. In summary, two out of the three studies of meningiomas and four out of the five studies of gliomas reported a statistically significant association between the brain cancer and infection with T. gondii [93][94][95][96].…”
Section: Other Diseases and Conditionsmentioning
confidence: 95%